Analisis Kebutuhan Air Bersih IPA PDAM Samboja Kutai Kartanegara - Irna Hendriyani; Martheana Kencanawati; Agus Nur Salam (Media Ilmiah Teknik Sipil, 2019)
The problem of providing clean water is currently a special concern for developed countries and developing countries. Indonesia as a developing country cannot be separated from the problem of providing clean water for its people. One of the main problems faced is the lack of available sources of clean water, the uneven distribution of clean water services, especially in rural areas and existing clean water sources that have not been utilized optimally. This study aims to analyze the clean water needs of PDAM Samboja which uses 2 pumps in the next 10 years (2028). By using primary and secondary data obtained from PDAM Samboja and a number of related references, it was found that the IPA clean water needs of PDAM Tirta Mahakam Samboja with 2 pumps, in 2018 amounted to 2,599.5 m3/day. With the estimated results of the number of customers in the next 10 years (2028), the number of water requirements is 3,048 m3/day. Therefore it is necessary to add 1 pump to the PDAM Samboja IPA so that it can still serve the needs of customers in the next 10 years